Integrating Local Culture into Digital Creativity (A Study on Digital Creative Economy Actors in Banda Aceh) - Taufik; Hermin Indah Wahyuni; Muhamad Sulhan (Profetik: Jurnal Komunikasi, 2025)
Although the digital infrastructure in Banda Aceh City is adequate, the growth of the digital creative economy in this region is still limited, especially in terms of integrating local culture into digital content. This study explores how cultural elements are involved in digital creative works by digital creative economy actors in Banda Aceh, with a primary focus on the sources of creative ideas and the mechanisms for implementing cultural elements. The novelty of this study lies in the use of Creative System Theory with an autopoiesis approach, which views creativity as an emerging process that arises from the interaction between external (hetero-referential) and internal (self-referential) elements. This study uses a qualitative approach with in-depth interview techniques with 19 digital creative economy actors from the music, film, animation, and application and game development sub-sectors. The results show that the sources of creative ideas include collaborative discussions, involvement in traditional practices, historical research, personal experiences, social anxiety, spiritual inspiration, studies of existing works, participation in creative communities, and institutional support. This diversity triggers an autopoietic cycle in the formation of ideas, where the relationship between internal interactions and external stimuli produces creative works that are full of cultural values. Cultural integration is realized through the digitalization of traditional music, culturally nuanced storytelling in films, folklore-based animations, and local-themed applications and games. Keywords: Digital Creativity, Digital Creative Economy, Creative Ideas, Creative System, Local Cultural.